2005
DOI: 10.1128/jcm.43.11.5574-5580.2005
|View full text |Cite|
|
Sign up to set email alerts
|

TaqMan Real-Time Reverse Transcription-PCR and JDVp26 Antigen Capture Enzyme-Linked Immunosorbent Assay To Quantify Jembrana Disease Virus Load during the Acute Phase of In Vivo Infection

Abstract: Jembrana disease virus (JDV) is an acutely pathogenic lentivirus that affects Bali cattle in Indonesia. The inability to propagate the virus in vitro has made it difficult to quantitate JDV and determine the kinetics of virus replication during the acute phase of the disease process. We report for the first time two techniques that enable quantification of the virus and the use of these techniques to quantify the virus load during the acute phase of the disease process. A one-step JDV pol TaqMan Jembrana dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Laboratorically, the notified major changes in haematological condition included a normocytic normochronic anaemia, leucopenia (particularly lymphopenia, eosinopenia and a slight neutropenia), a mild thrombocytopenia, elevated blood urea concentrations and reduced total plasma protein (Soesanto et al, 1990). Viruses are also detected in a high titer (up to 10 8 ID 50 /mL, equaling to 10 10 to 10 11 viral genome copies/ml) in the plasma fraction of the blood during the febrile state Soesanto et al, 1990;Stewart et al, 2005). The majority infected animals cultivate possible amount of antibodies to be detected only 6 weeks or more after recovery from the acute phase of the natural disease (Hartaningsih et al, 1994).…”
Section: Pathology Of Jembrana Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Laboratorically, the notified major changes in haematological condition included a normocytic normochronic anaemia, leucopenia (particularly lymphopenia, eosinopenia and a slight neutropenia), a mild thrombocytopenia, elevated blood urea concentrations and reduced total plasma protein (Soesanto et al, 1990). Viruses are also detected in a high titer (up to 10 8 ID 50 /mL, equaling to 10 10 to 10 11 viral genome copies/ml) in the plasma fraction of the blood during the febrile state Soesanto et al, 1990;Stewart et al, 2005). The majority infected animals cultivate possible amount of antibodies to be detected only 6 weeks or more after recovery from the acute phase of the natural disease (Hartaningsih et al, 1994).…”
Section: Pathology Of Jembrana Diseasementioning
confidence: 99%
“…It has been shown that disease transmission possibly occurs when the virus titer is above a threshold below which the risk of disease transmission is highly reduced. In Jembrana disease, the threshold is thought to be 10 6 genome copies/mL in plasma, equivalent to 10 4 ID50/mL in plasma and a titer of 10 10 -10 11 genome copies/ml is currently observed during the febrile state Soesanto et al, 1990;Stewart et al, 2005). Due to the high titers of infectious viral particles, virus transmission is most likely to occur during the acute phase.…”
Section: Jdv Vaccine Efficacymentioning
confidence: 99%